Constitutive expression of Cas9 and rapamycin-inducible Cre recombinase facilitates conditional genome editing in Plasmodium berghei - Samhita Das; Tanaya Unhale; Carine Marinach; Belsy del Carmen Valeriano Alegria; Camille Roux; Hélène Madry; Badreddine Mohand Oumoussa; Rogerio Amino; Shiroh Iwanaga; Sylvie Briquet; Olivier Silvie (Scientific Reports)
Abstract Malaria is caused by protozoan parasites of the genus Plasmodium and remains a global health concern. The parasite has a highly adaptable life cycle comprising successive rounds of asexual replication in a vertebrate host and sexual maturation in the mosquito vector Anopheles. Genetic manipulation of the parasite has been instrumental for deciphering the function of Plasmodium genes. Conventional reverse genetic tools cannot be used to study essential genes of the asexual blood stages, thereby necessitating the development of conditional strategies. Among various such strategies, the rapamycin-inducible dimerisable Cre (DiCre) recombinase system emerged as a powerful approach for conditional editing of essential genes in human-infecting P. falciparum and in the rodent malaria model parasite P. berghei. We previously generated a DiCre-expressing P. berghei line and validated it by conditionally deleting several essential asexual stage genes, revealing their important role also in sporozoites. Another potent tool is the CRISPR/Cas9 technology, which has enabled targeted genome editing with higher accuracy and specificity and greatly advanced genome engineering in Plasmodium spp. Here, we developed new P. berghei parasite lines by integrating the DiCre cassette and a fluorescent marker in parasites constitutively expressing Cas9. Owing to the dual integration of CRISPR/Cas9 and DiCre, these new lines allow unparalleled levels of gene modification and conditional regulation simultaneously. To illustrate the versatility of this new tool, we conditionally knocked out the essential gene encoding the claudin-like apicomplexan micronemal protein (CLAMP) in P. berghei and confirmed the role of CLAMP during invasion of erythrocytes.